Pengaruh penerapan standar akuntansi pemerintahan, kinerja keuangan, opini audit, dan pencegahan fraud terhadap kualitas laporan keuangan pemerintah daerah - Ayu Kurnia, Alifia; Jaeni, Jaeni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the effect of the influence of the application of Government Accounting Standards, Financial Performance, Audit Opinion, And Fraud Prevention on The Quality of Local Government Financial Reports. This research is a quantitative study. The population used is the audited financial statements of district/city government throughout Central Javwa in 2018-2020. This study uses secondary data sourced from the website of each local government. Purposive sampling is the method used in this study to obtain 105 samples of observational data from 35 districts/cities government throughout Central Java. In this study, the data analysis technique used is logistic regression analysis. This study shows the results that the application of Accounting Standards and Audit Opinions has a positive and significant effect on The Quality of Local Government Financial Reports. Meanwhile, Financial Performance have no positive and significant effect on The Quality of Local Government Financial Reports and Fraud Prevention have no negative and significant effect on The Quality of Local Government Financial Reports.